ISLAMIC BOARDING SCHOOL MANAGEMENT IN IMPROVING STUDENT QUALITY (Case Study in the Boarding School of Tahfidzul Qur'an Mifahul Huda Karawang ) - Habibullah Abdurrahman; Nandang Rukanda (IKIP Siliwangi Bandung, 2020)
The background of this research is that the management of Islamic boarding schools in Indonesia still use traditional management systems. by only doing learning without good management. Good boarding school management is expected to produce high-quality students. The research objective is the management of Islamic boarding schools in improving the quality of students.The theoretical basis used is management theory, boarding school theory, student theory. Methods research use interviewing techniques and observation with qualitative descriptive methods to obtain information from sources. The sample in this study was chosen randomly on the grounds that the sample chosen was an influential person in the study as well as many people who were directly involved in the process whose information the researchers needed. The sample chosen was one manager of the Islamic boarding school, one teaching staff, and five people student location of the study was conducted at Pondok pesantren tahfidzul Qur'an miftahul huda Karawang West Java. The results of this study are changes in management that occur in boarding schools have a very big influence on changes in the quality of students.The conclusion of this study is that Islamic boarding school as a traditional Islamic education system that has been transformed into a modern system has played a significant role in shaping the quality of Indonesian human resources.